An immersive educational tool for dental implant placement: A study on user acceptance. (February 2021) - Zorzal, Ezequiel Roberto; Paulo, Soraia Figueiredo; Rodrigues, Pedro; Mendes, José João; Lopes, Daniel Simões
Graphical abstract: Highlights: A Virtual Reality system to assist in learning implant placement. Improves visualization and representation of oral anatomy. Implants can be placed virtually into their ideal positions related to the planned restorations. Free-hand interaction provides additional degrees of freedom and valuable geometrical information. A study on user acceptance with dentistry professionals. Abstract: Background: Tools for training and education of dental students can improve their ability to perform technical procedures such as dental implant placement. Shortage of training can negatively affect dental implantologists' performance during intraoperative procedures, resulting in lack of surgical precision and, consequently, inadequate implant placement, which may lead to unsuccessful implant supported restorations or other complications. Objective: We designed and developed IMMPLANT a virtual reality educational tool to assist implant placement learning, which allows users to freely manipulate 3D dental models (e.g., a simulated patient's mandible and implant) with their dominant hand while operating a touchscreen device to assist 3D manipulation. Methods: The proposed virtual reality tool combines an immersive head-mounted display, a small hand tracking device and a smartphone that are all connected to a laptop. The operator's dominant hand is tracked to quickly and coarsely manipulate either the 3D dental model or the virtual implant, while the non-dominant hand holds a smartphone converted into a controller to assist button activation and a greater input precision for 3D implant positioning and inclination. We evaluated IMMPLANT's usability and acceptance during training sessions with 16 dental professionals. Results: The conducted user acceptance study revealed that IMMPLANT constitutes a versatile, portable, and complementary tool to assist implant placement learning, as it promotes immersive visualization and spatial manipulation of 3D dental anatomy. Conclusions: IMMPLANT is a promising virtual reality tool to assist student learning and 3D dental visualization for implant placement education. IMMPLANT may also be easily incorporated into training programs for dental students.